Desarrollo de las macro destrezas, escuchar- hablar para la resolución de conflictos en el sexto año de la Escuela de educación básica “García Moreno” en el periodo lectivo 2021-2022 - López Ponce, Daniela Alejandra (2022)
The present research aimed to analyze the development of macro listening and speaking skills for conflict resolution. Being able to recognize, select, anticipate and interpret the message, phrases, and words helps the development of selective, analytical, empathetic, and active listening; these skills are relevant to planning the speech, negotiating the meaning, and knowing the verbal code, delivering solutions effectively and positively to the problems that arise inside and outside the classroom. Methodologically, the qualitative approach was used, with a non-experimental design, descriptive, field, and documentary type, at the exploratory level. The population was made up of 35 sixthyear students of Escuela de Educación Básica “García Moreno” as a technique, observation, and the instrument, the observation sheet, which allowed data analysis; it was concluded that conflict resolution should work through processes, which allows relating the macro listening and speaking skills for conflict resolution, it is relevant to recognize the keywords and phrases of communication, as well as to select, anticipate, interpret and retain the message. In the same way, planning the discourse, negotiating the meaning, and recognizing the non-verbal code, will allow generating a solution to the conflict.